Ultrafast time-resolved photoelectron spectroscopy of substituted benzene molecules - Whalley, Laura Elizabeth (2020)
Intramolecular vibrational energy redistribution, IVR, is a non-radiative process of energy dispersal throughout polyatomic molecules through the coupling of vibrational modes. IVR is an important consideration for molecular stability and chemical reactivity. The experiments within this thesis have utilised laser pulses of ~1 ps duration, which are sufficiently short to monitor IVR dynamics that typically occur on a picosecond timescale, whilst having a sufficiently narrow bandwidth to allow (partial) resolution of vibrational levels. In this work, the vibrational levels of para-fluorotoluene (pFT) and aniline in the first electronically excited state (S1) have been identified using resonance enhanced multiphoton ionisation (REMPI) in combination with slow electron velocity map imaging (SEVI) which is used to investigate the cationic ground state. IVR dynamics within the S1 electronic state of these molecules have been probed using time-resolved photoelectron spectroscopy, also utilising the technique of velocity map imaging (VMI). IVR dynamics that occur following the excitation of two near-degenerate vibrational levels at S1 00 + ~2000 cm-1 in pFT have been investigated. In both cases doorway states which mediate the IVR dynamics have been identified, and IVR lifetimes, which differ dramatically for the two levels, have been determined. The IVR dynamics associated with these two levels are concluded to be mode- specific. A systematic study of IVR in the S1 electronic state of aniline has been conducted. Assignments have been made for S1 vibrational levels up to S1 00 +2110 cm-1. These S1 vibrational levels were then used as intermediates in the time-resolved study. Different IVR regimes have been observed with changing wavenumber; the lowest wavenumber vibrations exhibited no time-dependence indicating that no IVR redistribution processes occurred. With increasing wavenumber, vibrational levels exhibited quantum beats typical of restrictive IVR, in which populations remain localised between a few vibrational modes. The highest wavenumber vibrational levels either showed quantum beats alongside overall decay, indicative of doorway states mediating the dynamics, or fast ‘dissipative’ energy dispersal.